WEIGHT TRAINING IN GYMS OF CLUJ-NAPOCA AS LEISURE PHYSICAL ACTIVITY: WARM-UP AND COOL-DOWN PHASES - Remus-Cristian VĂIDĂHĂZAN; Iacob HANȚIU; Adelina STAICU (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2016)
The human body becomes more efficient as it reaches adequate levels of physical fitness. Practicing regular exercise combined with good nutrition decreases the time needed for recovery and reconstruction of all tissues (Bushman, Clark-Young, & American College of Sports Medicine, 2005). The type of activities that people practice lifelong determines their functional capacity that they will keep for their own musculoskeletal system, with important implications for the whole body. The practice of weight training plays an important role in delaying and reducing the negative effects that aging has on the human body (American College of Sports Medicine, 2013). Objective of the study: The objective of this study was to investigate the weight training practiced as a leisure activity in Cluj-Napoca's fitness gyms. We were interested in methodical approach implemented by practitioners for warm-up and cool-down. Methods: The research was conducted from 14 August 2013 to 20 August 2014 in Cluj-Napoca's weight training gyms. The subjects were practitioners of all gyms where weight training is practised, and where we were granted access. We registered between 4 and 6 practitioners in every gym. A total of 155 practitioners were interviewed, 81 of them accepted to participate to our study. Conclusions: The methodical approach of weight training workouts is faulty for many practitioners. For most of them, the warm-up phase does not present proper importance and the majority of practitioners do not do it right. The situation is even worse if we analyse the implementation of cool-down phase. This part of workout is missing to almost all practitioners. Practitioners of weight training does not relate to dynamics of heart rate when they plan the warm-up and the cool-down for their workout. The heart rate dynamics recorded for weight training workouts were on a wide range of values. Practitioners presented different approaches and the lack of research it is a demand for all of us to continue the research in this field.